2005
DOI: 10.1002/jnr.20414
|View full text |Cite
|
Sign up to set email alerts
|

Tau is not normally degraded by the proteasome

Abstract: Tau-positive inclusions in neurons are consistent neuropathologic features of the most common causes of dementias such Alzheimer's disease and frontotemporal dementia. Ubiquitinated tau-positive inclusions have been reported in brains of Alzheimer's disease patients, but involvement of the ubiquitin-dependent proteasomal system in tau degradation remains controversial. Before considering the tau degradation in pathologic conditions, it is important to determine whether or not endogenous tau is normally degrade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
(41 reference statements)
2
38
0
Order By: Relevance
“…It has been reported that tau is not normally degraded by the proteasome given the fact that tau degradation by proteasome requires polyubiqutination of tau but it is difficult to observe polyubiqutinated tau in cells [23]. It has been suggested that autophagy might play a key role in the degradation of protein aggregates in age-related neurodegenerative diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tau is not normally degraded by the proteasome given the fact that tau degradation by proteasome requires polyubiqutination of tau but it is difficult to observe polyubiqutinated tau in cells [23]. It has been suggested that autophagy might play a key role in the degradation of protein aggregates in age-related neurodegenerative diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicate that the expression of MAP proteins can be regulated by activation of calpain proteolytic pathway (Buddle et al, 2003) and, to a lesser extent, by the proteasomal pathway (David et al, 2002;Feuillette et al, 2005). Therefore, to investigate possible mechanisms involved in Tatmediated MAP2 breakdown, we treated Tat-expressing neurons with specific inhibitors of the calpain or proteasome pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Tau is generally thought to be a target for proteasome degradation but some recent data challenge this assertion (Cardozo and Michaud, 2002;David et al, 2002;Feuillette et al, 2005;Petrucelli et al, 2004). One report suggests that application of the protein synthesis blocker, cyclohexamide, increases tau levels, which are then further augmented by the application of a proteasome inhibitor, whereas application of the proteasome inhibitor alone actually resulted in a decrease in tau levels (Feuillette et al, 2005).…”
Section: In Vivo Inhibition Of the Proteasome Induces Aβ And Tau Accumentioning
confidence: 99%
“…One report suggests that application of the protein synthesis blocker, cyclohexamide, increases tau levels, which are then further augmented by the application of a proteasome inhibitor, whereas application of the proteasome inhibitor alone actually resulted in a decrease in tau levels (Feuillette et al, 2005). We examined the effects of proteasome inhibition on tau degradation by transiently transfecting HEK cells with wildtype human tau (2N/4R) and treating a subset of these cells with 10 μM epoxomicin for 12 h, as previous work indicated that the half-life of tau in cells is about 12-14 h (David et al, 2002).…”
Section: In Vivo Inhibition Of the Proteasome Induces Aβ And Tau Accumentioning
confidence: 99%